A Comparision of Bearing Capacity of Pile from Pile Driving Formulas and Dynamic Load Test - โพธิ์จันทร์, วรวิทย์; ลี้อนันต์ศักดิ์ศิริ, อนุชาติ; ป้องนาม, ฐิตินันท์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The objective of this research in to evaluate the bearing capacity of pile by using pile driving formulas such as Hiley’s Formula, Engineering News Formula, Danish Formula and Janbu’s Formula to compare, relationship between and the optimum factor of safety with Dynamic Load Test results. The ultimate load of a pile was calculated process by Case Pile Wave Analysis Program (CAPWAP). The Results showed that the pile driving formulas that was similar of ultimate bearing capacity by Dynamic Load Test was Hiley’s Formula, Engineering News Formula, Danish Formula and Janbu’s Formula, respectively. Whereas the Hiley’s Formula provides the most reliable and close test results (R2 = 0.831), Danish Formula and Janbu’s Formula have a chance to fail if used. Furthermore, by using the factor of safety recommended by E.I.T. to reduce load carrying capacity from each all of pile driving formulas are safe, Hiley’s Formula and Engineering New Formula is lower load, making it very safe but the construction costs will increase. The researcher found the appropriate safety factor of each formulas as follows Hiley’s Formula, Engineering News Formula, Danish Formula and Janbu’s Formula are equal to 2.5499, 2.2555, 3.7095 and 4.2525 respectively.